Synergistic Interaction of Arbuscular Mycorrhizal Fungi and Phosphate-Solubilizing Bacteria with NPK Fertilizer to Improve Sorghum bicolor (L.) Moench Growth under Saline Condition - Indriati Ramadhani; Sri Widawati (Indonesian Society for microbiology, 2020)
ABSTRACT Sweet sorghum (Sorghum bicolor (L.) Moench) is a food source and a raw material in biofuel-ethanol production. Arbuscular mycorrhizal fungi (AMF) and phosphate-solubilizing bacteria (PSB) are called rhizosphere microorganisms, which are useful microorganisms that enhance plant growth. Rhizosphere microorganisms also increase plant's resistance to environmental stress, while NPK fertilizer used on agricultural land are found to increase crop yields only. However, its continuous application has a negative impact on the environment. Therefore, this research aimed to study the synergy between AMF, and PSB with NPK fertilizer in influencing the sweet sorghum growth in saline condition. Two treatment factors were used, which are microbes combination (arbuscular mycorrhizal fungi and phosphate-solubilizing bacteria), and NPK doses without NPK, 25% NPK, 50% NPK, and 100% NPK. Furthermore, zeolite was used to grow sweet sorghum seeds individually and were maintained for one month in a greenhouse. Pots were watered with 50% seawater (freshwater: seawater = 1:1) every day to keep the moisture. Plant growth parameters were also measured, which includes AMF colonization in the roots, number of AMF spores, and PSB population in the planting medium. The combination of AMF, PSB, and NPK in sweet sorghum increased the plant height, number of leaves, plant fresh weight, plant dry weight, and total of plant P, although not always significant. AMF+PSB+25% NPK produced the highest number in all parameters. Therefore, the synergy between AMF, and PSB with NPK fertilizer is able to increase the plant growth in saline condition. Key words: arbuscular mycorrhizal fungi, phosphate-solubilizing bacteria, NPK, saline, and sweet sorghum ABSTRAK Sorgum manis (Sorghum bicolor (L.) Moench) merupakan sumber makanan dan bahan baku dalam produksi bioetanol. Jamur mikoriza arbuskular (JMA) dan bakteri pelarut fosfat (BPF) disebut sebagai mikroorganisme rizosfer, yang merupakan mikroorganisme yang berguna untuk meningkatkan pertumbuhan tanaman. Mikroorganisme rizosfer juga meningkatkan ketahanan tanaman terhadap cekaman lingkungan, sedangkan pupuk NPK yang digunakan pada lahan pertanian ternyata hanya meningkatkan hasil panen saja. Namun, penerapannya yang berkelanjutan memiliki dampak negatif terhadap lingkungan. Oleh karena itu, penelitian ini bertujuan untuk mempelajari sinergi antara JMA, dan BPF dengan pupuk NPK dalam mempengaruhi pertumbuhan sorgum manis dalam kondisi salin. Dua faktor perlakuan yang digunakan, yaitu kombinasi mikroba (jamur mikoriza arbuskular dan bakteri pelarut fosfat), dan dosis NPK tanpa NPK, 25% NPK, 50% NPK, dan 100% NPK. Selanjutnya, zeolit digunakan untuk menumbuhkan biji sorgum manis secara individu dan dipelihara selama satu bulan di rumah kaca. Pot disiram dengan 50% air laut (air tawar: air laut = 1: 1) setiap hari untuk menjaga kelembaban. Parameter pertumbuhan tanaman juga diukur, yang meliputi kolonisasi JMA di akar, jumlah spora JMA, dan populasi BPF dalam media tanam. Kombinasi JMA, BPF, dan NPK dalam sorgum manis meningkatkan tinggi tanaman, jumlah daun, berat basah tanaman, berat kering tanaman, dan P total tanaman, meskipun tidak selalu signifikan. JMA + BPF + 25% NPK menghasilkan nilai tertinggi di semua parameter pertumbuhan. Oleh karena itu, sinergi antara JMA dan BPF dengan pupuk NPK mampu meningkatkan pertumbuhan tanaman dalam kondisi salin. Kata kunci: jamur mikoriza arbuskular, bakteri pelarut fosfat, NPK, salin, dan sorgum manis